Perceptions of the nursing profession among first-year health profession students: A cross-sectional study in Palestine - Kareem Sbaih; Mohammad Qtait; Nesreen Alqaissi; Fuad Farajalla (PLoS ONE, 2025)
Background Nursing plays a vital role in healthcare systems worldwide, yet in many societies including Palestine it remains undervalued and misunderstood. First-year health profession students’ perceptions of nursing influence academic engagement, career preferences, and interprofessional relationships. Recent Palestinian studies have shown that resilience, coping strategies, and exposure to clinical environments strongly affect how students view nursing as a profession. Objective To assess perceptions of the nursing profession among first-year health profession students at University, and explore the influence of sociodemographic characteristics and prior healthcare exposure. Methods A descriptive cross-sectional study was conducted among 214 first-year students in health-related programs between 10 March and 10 April 2025. Data were collected using a culturally adapted 26-item Nursing Image Scale (NIS). Descriptive statistics, t-tests, one-way ANOVA, multivariable regression, and ANCOVA were applied, with significance set at p < 0.05. Results The mean perception score was 3.99 out of 5 (79.8%), reflecting moderately positive attitudes. Nursing students reported slightly higher scores (80%) than non-nursing peers (78.4%). No significant differences were found by gender, residence, or family ties to nursing. However, prior hospital exposure was significantly associated with more favorable perceptions (p = 0.04). Regression analysis confirmed that gender, age, GPA, and prior clinical exposure predicted higher perception scores. Conclusion While overall perceptions of nursing were moderately positive, direct hospital exposure and academic achievement were linked to more favorable views. These findings suggest that integrating structured early clinical experiences and resilience-building strategies into curricula could strengthen the image of nursing in Palestine. Limitations The single-institution setting and use of convenience sampling limit generalizability, though findings remain valuable for regional nursing education policy.